European Union non-tariff barriers to imports of African biofuels - Franziska Schuenemann; William A. Kerr (Agrekon, 2019)
The introduction of EU mandates for biofuel use in the transport sector initially led to high expectations that African countries would benefit from biofuel exports to the EU. This market opportunity has not been realised, however, due to regulatory requirements for the production of biofuels that act as non-tariff barriers to the acceptance of African biofuels in the EU. This benefits producers of biofuel crops and processors in the EU by providing economic protection. In particular, the EU import regime fails to acknowledge the challenges faced by African (or other) developing countries in satisfying the requirements. Using a computable general equilibrium model for Malawi, we quantify the foregone potential benefits from biofuel production for exports to the EU arising from non-tariff barriers (NTBs) embedded in the sustainability criteria. Our results show that sugarcane-ethanol production under smallholder outgrower regimes would lead to both economic growth outcomes and rural development, whereas jatropha-biodiesel fails to increase rural incomes due to low profitability. While there is widespread agreement on the latter today, our study is the first to explore the failure of jatropha in Malawi in an economy-wide framework. The ethanol results, however, also hold if land clearing is forbidden, thereby preserving biodiversity as stipulated under the sustainability criteria in the EU Renewable Energy Directive. The EU NTBs embedded in the Renewable Energy Directive thus play a much larger role for countries in Sub-Sahara Africa than simply inhibiting investment opportunities and should be refashioned to lower the entry costs for developing countries.
Keywords: F13; D58; O13; Q17; 330; Non-tariff barriers; biofuels; Malawi; CGE model